The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/w13213045
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Phytoplankton Dynamics in Two Reservoirs in Southern Africa with Special Reference to Water Abstraction for Inter-Basin Transfers and Potable Water Production

Abstract: Toxic phytoplankton in the aquatic ecosystems are dynamic, affecting water quality. It remains unclear as to how possible toxic phytoplankton assemblages vary vertically and temporally in Swakoppoort and Von Bach dams, located in a dry subtropical desert region in central Namibia. The following variables were analyzed: pH, Secchi depths, turbidity, water temperature, total phosphorus, orthophosphate, chlorophyll-a, phytoplankton cells, and water depths. Cyanobacteria dominated the phytoplankton community in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Water quality parameters considered for analysis included common major cations (NH 4 + ), anions (NO 3 − , NO 2 − ), and one system water quality parameter (pH). Although there were missing periods from the 2001-2021 dataset that was used in this study, due to challenges of not sampling caused by the expired license registration of the boat and a lack of human capacity as well as financial constraints, the study used a long-term data set analysis [17] that proved to be sufficient to provide insights into the water quality of the dam. The study employed the analysis of annual mean concentrations, which were then presented with Microsoft Excel 2016 surface graphs that showed the temporal and spatial distribution of the selected parameters.…”
Section: Data Analysis 231 Statistical Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Water quality parameters considered for analysis included common major cations (NH 4 + ), anions (NO 3 − , NO 2 − ), and one system water quality parameter (pH). Although there were missing periods from the 2001-2021 dataset that was used in this study, due to challenges of not sampling caused by the expired license registration of the boat and a lack of human capacity as well as financial constraints, the study used a long-term data set analysis [17] that proved to be sufficient to provide insights into the water quality of the dam. The study employed the analysis of annual mean concentrations, which were then presented with Microsoft Excel 2016 surface graphs that showed the temporal and spatial distribution of the selected parameters.…”
Section: Data Analysis 231 Statistical Analysismentioning
confidence: 99%
“…Further unwanted effects of algal blooms include the generation of foul odor and a reduction in biodiversity [84,85]. The occurrence of potentially toxic cyanobacteria species in drinking water dams leads to the abstraction of poor raw water quality for inter-basin and potable water provision, and this could be more severe in subtropical dams located in climate regions characterized by low rainfalls and high evaporation, such as the Vaal Dam in South Africa and Swakoppoort Dam in Namibia [17].…”
Section: Overall Assessment Of Water Quality Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies on South Africa’s urban Molopo River depicted anthropogenic Cu, Cr, Zn, and Pb sediment contamination with potentially deleterious ecological impacts on the benthic algal and macrofauna communities (Mohajane and Manjoro 2022 ). Additionally, the diatom-based biomonitoring tools (e.g., the “South African Diatom Index (SADI)” and the “Benthic Diatom Index (BDI)”) have been used to detect and quantify the magnitude of natural and anthropogenic impacts on stream ecosystems (Lang et al 2013 ; Harding and Taylor 2014 ; Sirunda et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Reports have also shown that dams such as those at Vaal and Hartbeespoort are dominated by toxic cyanobacteria such as Dolichospermum and Microcystis sp. [4]. Toxic blooms present a threat to the South African population, since water derived from the impacted reservoirs is mainly used for drinking [3] and irrigation purposes [5].…”
Section: Introductionmentioning
confidence: 99%